Azithromycin Clears Bordetella pertussis Infection in Mice but Also Modulates Innate and Adaptive Immune Responses and T Cell Memory - Borkner, Lisa; Misiak, Alicja; Wilk, Mieszko M.; Mills, Kingston H. G. (Frontiers in Immunology, 2018)
Treatment with the macrolide antibiotic azithromycin is an important intervention for controlling infection of children with Bordetella pertussis and as a prophylaxis for preventing transmission to family members. However, antibiotics are known to have immunomodulatory effects independent of their anti-microbial activity. Here we used a mouse model to examine the effects of azithromycin treatment on clearance of B. pertussis and induction of innate and adaptive immunity. We found that treatment of mice with azithromycin either 7 or 14 days post challenge effectively cleared the bacteria from the lungs. The numbers of innate immune cells in the lungs were significantly reduced in antibiotic-treated mice. Furthermore, azithromycin reduced the activation status of macrophages and dendritic cells, but only in mice treated on d7. Early treatment with antibiotics also reduced the frequency of tissue-resident T cells and IL-17-producing cells in the lungs. To assess the immunomodulatory effects of azithromycin independent of its anti-microbial activity, mice were antibiotic treated during immunization with a whole cell pertussis (wP) vaccine. Protection against B. pertussis induced by immunization with wP was slightly reduced in azithromycin-treated mice. Antibiotic-treated wP-immunized mice had reduced numbers of lung-resident memory CD4 T cells and IL-17-production and reduced CD49d expression on splenic CD4 T cells after challenge, suggestive of impaired CD4 T cell memory. Taken together these results suggest that azithromycin can modulate the induction of memory CD4 T cells during B. pertussis infection, but this may in part be due to the clearance of B. pertussis and resulting loss of components that stimulate innate and adaptive immune response.